Integrative taxonomy does not support the occurrence of two species of the Squalius squalus complex (Actinopterygii, Cypriniformes, Cyprinidae) in Italy - Lucentini, Livia
The systematic is still unresolved for the genus Squalius (Cyprinidae, Leuciscinae), a rich group of small to large fishes widely distributed throughout Europe. The distinction of one of the Italian narrowly endemic species, Squalius albus (Bonaparte, 1838), described for the area surrounding lake Trasimeno, from the more common and widespread Squalius squalus (Bonaparte, 1837) is doubtful. The application of integrative taxonomy, with DNA taxonomy and quantitative morphometric, using both living and preserved individuals collected from lake Trasimeno before Squalius sp. restocking, allowed us to explicitly test for the identity of the two species in the complex. COI barcoding data, used for phylogenetic reconstructions, underlined that two clades may exist in the complex; nevertheless, DNA taxonomy (ABGD and GMYC) and morphometrics show no statistical support for their identity as separate species. Moreover, during our survey of the genetic diversity of the Italian Squalius, we provided further support for the species status of Squalius lucumonis, and found evidence of the occurrence in Southern Italy of another chub species, Squalius vardarensis (Karaman, 1928), previously known only from the Southern part of the Balkan Peninsula.